THE EFFECT OF PRICE PERCEPTION, QUALITY PERCEPTION, AND LOCATION ON PURCHASE DECISIO - I Made Bagus Dwiarta; Riza Wahyu Ardiansyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Today's business development is getting more crowded, and it makes people unable to fulfill their personal wants and needs. In fulfilling human food needs, we are faced with many choices, one of which is fast food. The choice to buy fast food is inseparable from outlet management efforts to provide satisfaction to its customers. This study aims to analyze the effect of perceived price, perceived quality, and location on purchasing decisions at BFC Duo Buduran Sidoarjo. The analytical method used is multiple regression. The population in this study were all consumers of BFC Duo Buduran Sidoarjo with a sample of 119 respondents. The technique used for sampling is incidental sampling. The results showed that partially the price perception, perceived quality, and location had a significant and positive effect on purchasing decisions at BFC Duo Buduran Sidoarjo.